On Your Mark, Get Set, Choose! A Randomized Cross-Over Study Comparing Fixed and Self-Selected Rest Periods in Interval Running Among Professional Female Soccer Players - Asaf Ben-Ari; Yedidya Silverman; Uri Obolski; Israel Halperin (Sports Medicine - Open)
Abstract Background Studies on rest durations during high-intensity interval training (HIIT) often compare fixed and self-selected (SS) rest allocation approaches. Frequently, the rest duration under SS conditions is unlimited, leading to inconsistent total rest durations compared to fixed rest conditions. To address this limitation, we recently compared fixed and SS rest conditions during cycling HIIT sessions, while keeping the total rest duration equivalent. However, our protocol required athletes to divide a long total rest duration (720 s) across nine intervals, which may have been overly cognitively demanding. The current study aimed to explore the effects of the SS approach with a simplified rest allocation task on performance, physiological, and psychological outcomes. Methods Following a familiarization session, 24 professional female soccer players completed two running HIIT sessions on a non-motorized treadmill. Each session consisted of twelve 15 s intervals, divided into three blocks, with the goal of maximizing the distance covered. In both conditions, the between-interval rest duration per block amounted to 270 s. In the fixed condition, the rest was uniformly allocated to 90 s between each interval, whereas in the SS condition, the athletes chose how to allocate the entirety of the 270 s of rest. We compared the following outcomes: distance, heart rate, perception of fatigue, effort, autonomy, enjoyment, boredom, and athletes’ preferences. Outcomes were compared using aggregated measures via paired univariate tests, and across the intervals via mixed-effects models. Results We observed comparable results in most outcomes with the exception of higher autonomy (1–15 points) in the SS condition (mean difference = 2.1, 95%CI (0.9, 3.3) points) and a negligibly higher heart rate in the SS condition when comparing the observations across intervals (estimate = 2.5, 95%CI (0.9, 4.2) beats × min−1). Additionally, participants chose to rest for longer durations as the block progressed. Finally, the majority of participants (65%) favored the SS condition. Conclusion This study further solidifies that SS and fixed approaches with matched total rest durations result in similar performance, physiological, and psychological responses. This effect persists even when the total rest duration required to be allocated is relatively short. Therefore, coaches and trainees can choose either approach based on their preferences and training goals.